Mycobacterium tuberculosis Rv0494 Protein Contributes to Mycobacterial Persistence - Ji L; Jiang T; Zhao X; Cai D; Hua K; Du P; Chen Y; Xie J (Infection and Drug Resistance, 2023)
Lei Ji,1 Tingting Jiang,1 Xin Zhao,2 Damin Cai,1 Kouzhen Hua,1 Peng Du,1 Yuanyuan Chen,3 Jianping Xie4 1School of Basic Medical Sciences and Forensic Medicine, Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 2Department of International Registration, Ustar Biotechnologies (Hangzhou) Ltd, Hangzhou, Zhejiang, People’s Republic of China; 3Tuberculosis Diagnosis and Treatment Center, Hangzhou Red Cross Hospital, Hangzhou, Zhejiang, People’s Republic of China; 4Institute of Modern Biopharmaceuticals, State Key Laboratory Breeding Base of Eco-Environment and Bio-Resource of the Three Gorges Area, Key Laboratory of Ministry of Education Eco-Environment of the Three Gorges Reservoir Region, Ministry of Education, Chongqing Municipal Key Laboratory of Karst Environment, School of Life Sciences, Southwest University, Chongqing, People’s Republic of ChinaCorrespondence: Lei Ji, School of Basic Medical Sciences and Forensic Medicine, Hangzhou Medical College, No. 481 Binwen Road, Hangzhou, Zhejiang, 310053, People’s Republic of China, Tel +86 571 8769 2681, Fax +86 571 8769 2673, Email jilei@hmc.edu.cnPurpose: Fatty acid metabolism plays an important role in the survival and pathogenesis of Mycobacterium tuberculosis. During dormancy, lipids are considered to be the main source of energy. A previous study found that Rv0494 is a starvation-inducible, lipid-responsive transcriptional regulator. However, the role of Rv0494 in bacterial persister survival has not been studied.Methods: We constructed a Rv0494 deletion mutant strain of Mycobacterium tuberculosis H37Rv and evaluated the susceptibility of the mutant strain to antibiotics using a persistence test.Results: We found that mutations in Rv0494 lead to survival defects of persisters, which reflected in increased sensitivity to isoniazid.Conclusion: We conclude that Rv0494 is important for persister survival and may serve as a good target for developing new antibiotics that kill persister bacteria for improved treatment of persistent bacterial infections.Keywords: drug target, drug tolerance, lipids, persisters